From exciton resonance to frequency mixing in GaAs multiple quantum wells - Ahn, YH; Yahng, JS; Sohn, JY; Yee, KJ; Hohng, SC; Woo, JC; Kim, DS; Meier, T; Koch, SW; Lim, YS; Kim, EK (AMER PHYSICAL SOC, 1999)
Frequency mixing (2 omega(1) - omega(2)) is demonstrated in femtosecond nondegenerate four-wave mixing (FWM) on GaAs multiple quantum wells using two synchronized, independently tunable lasers. The frequency mixing component in the spectrally resolved FWM coexists with the exciton resonance, and it dominates over the exciton component at high intensity and high detuning. This off-resonant component is present only for delays smaller than the temporal pulse width, whereas the resonant exciton component survives for longer delays.
Keywords: FEMTOSECOND